(g o f)(x)=12x²+16 x-3 ,f(x)=3x²+4x-3, find g(x)

2 answers

(g o f)(x)
is the same as f(g(x))

Observing that
12x^2 + 16x - 3
= 4(3x^2 + 4x) - 3

let g(x) = 4x

then f(g(x))
= 3(4x)^2 + 4(4x) - 3
= 12x^2 + 16x - 3 , which is what we have, so

g(x) = 4x
Hmmm. I thought (g o f)(x) was g(f(x)).

If that is so,
12x^2 + 16x - 3 = 4(3x^2 + 4x - 3) + 9
= 4f+9

so g(x) = 4x+9
Similar Questions
  1. What is the simplified form of (3x + 2)(4x – 3)? Use a table.(1 point) Responses 12x2 + 18x + 6 12 x 2 + 18 x + 6 12x2 + x –
    1. answers icon 1 answer
  2. What is the simplified form of (3x + 2)(4x – 3)? Use a table.(1 point) Responses 12x2 + 18x + 6 12 x 2 + 18 x + 6 12x2 + x –
    1. answers icon 1 answer
  3. What is the simplified form of (3x + 2)(4x – 3)? Use a table.(1 point) Responses 12x2 + 18x + 6 12 x 2 + 18 x + 6 12x2 + x –
    1. answers icon 1 answer
  4. Find the product: W×G W=3x−2 and G=4x−1(1 point) Responses 12x2−5x−2 12x2−11x+2 7x2−9x−2 x2−10x+2
    1. answers icon 1 answer
more similar questions